Comparison of hemodynamic responses of intravenous dexmedetomidine and esmolol infusion during laparoscopic cholecystectomy - Zuberi, Azka; Tiwary, Vaibhav; Rastogi, Bhawana; Gupta, Kumkum; Kumar, Abhishake; Farooqui, Raza (International Journal of Research in Medical Sciences, 2018)
Background: Laparoscopic cholecystectomy is one of the commonest surgery performed under general anesthesia in this set up but maintaining the hemodynamic stability is challenging in these patients. The present study was conducted to comparatively analyse the hemodynamic variations using intravenous dexmedetomidine and intravenous esmolol during laparoscopic cholecystectomy. Methods: Study was conducted on 90 adult patients aged 18-60 years, of ASA grade I or II of both gender, scheduled for laparoscopic cholecystectomy under general anesthesia. Patients were randomized into three groups of 30 patients each. Patients of Group A received esmolol infusion (loading: 1mg/kg and maintenance: 5-15µg/kg/min), patients of Group B received dexmedetomedine infusion (loading: 0.7µg/kg and maintenance: 0.4µg/kg/hr) and Group C (control group) received normal saline infusion. Patients were monitored for changes in heart rate, ECG, systemic blood pressure and EtCO2, at baseline, at 5 min and 10 min after giving study drug bolus, after induction, intubation, skin incision and CO2 insufflation. Thereafter, these changes were recorded at 15 min intervals till the end of surgery. Results: It was observed that perioperative use of dexmedetomidine and esmolol infusions maintained better hemodynamic stability as compared to the normal saline in control group. Though the patients in esmolol group showed less fluctuations in BP and HR (as compared to control group), but, stability was better in the patients of dexmedetomidine group at all-time intervals. Conclusions: Dexmedetomidine infusion was a better option for maintaining hemodynamic stability in comparison to emolol infusion during laparoscopic surgeries.